Sinergi Pemerintah dan Perguruan Tinggi menuju Desa Maju dan Bermartabat melalui Implementasi Program Desa Sejahtera Mandiri - Diyanayati, Kissumi; Suryani, nfn; Hidayatullah, A. Nururrochman (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This study used a combined approach that were quantitative and qualitative (mix methods). The location of the research and data sources were determined by purposive sampling which was five universities with five districts with each of the two DSM program implementations. The five universities are UNJA (Muaro Jambi), UIN Antasari (Tapin), UNHAS (Bantaeng), UNEJ (Jember), and UNISSULA (Semarang). The research data source per location is 30 people consist of 10 college universities (lecturers and KKN students), social institution and related offices /institutions including 10 regency business district, village apparatus and PSKS program implementer including 10 person program companion. the total number of respondents were 150 people. Crosscheck performance outcomes were performed on four members of the beneficiary community. The results of the study found that stakeholders still have a poor understanding of the DSM program. Proven in five research sites cumulatively majority of respondents (55.33%) are less understood, 32.67 percent understood enough, and only 12 percent who understand. Respondents who understand came from DSM program managers of higher education and local social services. Respondents who do not understand about DSM program reach 55.33 percent comes from elements of KKN students, related OPD officials outside the social service and village officials. Understanding of DSM program due to lack of whereby socialization activities. Nevertheless, target villages such as village apparatus, Karang Taruna, TKSK, PKH facilitators, and community leaders are ready to make changes according to the objectives of the DSM program so that the community will be more prosperous and become an independent village. The third year of DSM program implementation in five locations found that the activities undertaken by universities are still limited to pioneering activities ideally done in the first year (2015). There is no visible coordination of universities with the district government so that has not been prepared synergy program between the OPD for the target village. Development program run partially by the OPD in accordance with the duties and functions of each. In order for DSM to achieve optimal results, it is recommended to socialize DSM program from the central level to the village location and to form taskforce /task force for DSM program implementation at the district level. Higher Education as the main companion of DSM program need to arrange planning activities in the form of roadmap which contains stage of activity and involvement of various parties Â 